(untitled) (Indian Journal of Chemistry (IJC), 2024)
5-Methylpyrazolo[1,5-a]pyrimidine derivatives were synthesized with starting materials that were either commercially or easily available. This was achieved by the ultrasound irradiation of 3-amino-1H-pyrazoles (3-7) and enaminones (2) assisted by KHSO4 in aqueous medium. The structures were established by spectral and analytical techniques. An X-ray crystallographic study of compound N-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)-7-(4-methoxyphenyl)-5-methylpyrazolo[1,5-a]pyrimidine-3-carboxamide (8b) confirmed the structural orientation and eliminated any ambiguity pertaining to its regioselectivity. Its space group is P21/n with the following unit cell parameters: a = 17.5775 (8), b = 7.1707 (4), c = 18.113 (1) Å, β = 91.449 (2) and Z = 4. Crystal structure was solved to a final R value of 0.062 and to a GOOF value of 1.09. Molecular docking of the compounds was executed to identify the potential antiviral and anticancer agents. Moreover, Molecular dynamics simulation study of the ligand 9c in a complex with 3pp0, revealed the stability of the potential ligand candidate 9c.